Design for kids - Exley, Sharon; Exley, Peter (Victoria, Australia : The Images Publishing Group Pty Ltd., 2007)
Peter Exley, FAIA and Sharon Exley are teachers, educative designers, and generators of good ideas; together they have amassed an impressive portfolio of interactive environments for children. Their firm, architectureisfun, develops architecture, interiors, exhibits, and learning resources for clients interested in sensorial and enlightened experiences as part of daily life. This publication examines architectureisfun's unique methodology that integrates architecture, learning, design and experience in its award-winning projects designed specifically for children. Kids on the Fly at Chicago's O'Hare International Airport is one such project. This soaring exhibit received an American Institute of Architects Interior Architecture Award and is recognised for its universality, accessibility, safety, and design. It is just one of the inventive, original and memorable projects included in this book.
Foreword -- Introduction -- Play with Architecture -- Architectural -- Out-of-doors -- Experiental -- Exploratory -- Public -- Cultural -- Spiritual -- Multi-generational.
Keywords: ARCHITECTUREISFUN (FIRM)